Development of 18F radiochemistry for positron emission particle tracking (PEPT) - Camroodien, Ameerah (Department of Physics, 2024)
Positron emission particle tracking (PEPT) is a non-invasive tracer-based measurement technique used to obtain dynamic information about multiphase systems. The basis of the technique is to radiolabel a phase-representative tracer particle with a positron emitting radionuclide. Electron-positron annihilation produces pairs of back-to-back 511 keV gamma photons emitted from the locality of the tracer particle. Pairs of annihilation photons are detected within the field-of-view of a modified positron emission tomography (PET) scanner, and the instantaneous position of the tracer particle is determined in three dimensions using reconstruction of consecutive annihilations via an iterative algorithm. From the continuously measured tracer particle trajectory, the time differential is used to produce velocity (and acceleration) fields, and further trajectory analysis reveals the localised behaviour of the tracer in the system under study including residence times and kinematic properties. For optimum tracking the radioactivity in a single particle must be sufficient irrespective of the tracer size and material. Typically activities in the range 250 µCi – 2 mCi are required, often loaded on to particles in the 10 mm - 100 µm diameter range. The physical properties of the tracer must accurately reflect those of the bulk media under study such that the measured PEPT data is reflective of the bulk motion. In this research a novel radiochemical technique in producing tracer particles from commercially available medical grade 18F-fluorodeoxyglucose (18F-FDG) (half-life 110 minutes) was developed. In the context of the radioisotopes and accelerated beams available through the National Research Foundation (NRF) accelerator facility iThemba LABS (Cape Town, South Africa), these methods offer the best, perhaps only, mechanism to utilising 18F-based radiotracers for PEPT in South Africa. Furthermore, this work reduces the need for daily isotope production by a dedicated cyclotron beam and the need for specialist equipment. Provided a suitable source of medical 18F-FDG can be sourced, PEPT is therefore possible without the site constraints of an accelerator facility, enabling wider applications of the technique. Compared to the 68Ga-based tracer particles (half-life 68 minutes) pioneered by PEPT Cape Town, 18F based 1 tracers have the distinct advantages of a longer half-life allowing for extended experimental timescales, and an increased signal to noise ratio from the pure β + emission with no additional gamma transitions. Commercially available medical grade 18F-FDG was utilised as the initial 18F stock. A column chromatography method was developed to separate the glucose-complex of 18F-FDG in preparation of the reactive solution, made of 18F in trifluoroacetic acid (TFA) complex, and used for radiolabelling. The anion exchange resins Purolite A870 and A200 were investigated for their ability to exchange non-radioactive counter ions for the required species. Ion exchange techniques were used to label small phase-representative tracer particles (<1 mm diameter) by controlled uptake of 18F. With limiting abundance effects, a loading solution composition of 1:2.5 of TFA:18F-FDG provided greatest uptake and activities of up to 100 µCi and 80 µCi were achieved for the A870 and A200 resins of diameter ranging from 430 - 590 µm respectively. The radiolabelling method was adjusted to incorporate pretreatment of the reactive solution prior to radiolabelling and yielded improved radiolabelling performance, resulting in 300 µCi and 200 µCi activities for the A870 and A200 resins of diameter ranging from 550 - 610 µm respectively. While the activity is still low with regards to optimum tracking, the methods developed here show potential for future tracer particle production. In some applications, particularly those with low attenuation and photon scattering, and/or small scale systems, the particles developed here are ideal.